More than the Money: Payoff-Irrelevant Terms in Relational Contracts - Erich Cromwell; Sebastian J. Goerg; Monika Leszczynska (Institute of Labor Economics (IZA), 2018)
We investigate how payoff-irrelevant terms can negatively impact relational contracts. In a lab experiment we compare two economically equivalent contracts – a fixed-term renewable and an open-ended at-will contract. Each contract provides partners with full flexibility regarding the length and termination of their interaction. When only one contract type is available, principals and agents in our experiment manage to form long-term profitable relationships irrespective of the contract type. However, when both contracts are available offering a fixed-term instead of an open-ended contract is perceived as unkind and results in lower effort provided by the agents. We show that this observed difference is not a matter of sorting, but a direct response to the contract type. Our results demonstrate that a relational contract might be affected by payoff-irrelevant terms and their perceived kindness.
Keywords: C92; K12; 330; contract design; relational contracts; reciprocity; trust